MET and autism susceptibility: family and case-control studies. - Sousa, I; Clark, T; Toma, C; Kobayashi, K; Choma, M; Holt, R; Sykes, N; Lamb, J; Bailey, A; Battaglia, A; Maestrini, E; Monaco, A (2009)
Autism is a common, severe and highly heritable neurodevelopmental disorder. The International Molecular Genetic Study of Autism Consortium (IMGSAC) genome screen for linkage in affected sib-pair families identified a chromosome 7q susceptibility locus (AUTS1), that has subsequently shown evidence of increased sharing in several independent multiplex samples and in two meta-analyses. Taking into account the location of the MET gene under this linkage peak, and the fact that it has recently been reported to be associated with autism, the gene was further analyzed as a promising autism candidate. The gene encodes a transmembrane receptor tyrosine kinase of the hepatocyte growth factor/scatter factor (HGF/SF). MET is best known as an oncogene, but its signalling also participates in immune function, peripheral organ development and repair, and the development of the cerebral cortex and cerebellum (all of which have been observed earlier as being disregulated in individuals with autism). Here we present a family-based association analysis covering the entire MET locus. Significant results were obtained in both single locus and haplotype approaches with a single nucleotide polymorphism in intron 1 (rs38845, P<0.004) and with one intronic haplotype (AAGTG, P<0.009) in 325 multiplex IMGSAC families and 10 IMGSAC trios. Although these results failed to replicate in an independent sample of 82 Italian trios, the association itself was confirmed by a case-control analysis performed using the Italian cohort (P<0.02). The previously reported positive association of rs1858830 failed to replicate in this study. Overall, our findings provide further evidence that MET may play a role in autism susceptibility.